RNAi verifications on olfactory defects of an essential biocontrol agent Agasicles hygrophila (Coleoptera: Chrysomelidae) regarding mating and host allocation - Ning, Xiaoyu; Huang, Cong; Dong, Changhong; Jin, Jisu; Qiao, Xi; Guo, Jianying; Qian, Wanqiang; Cao, Fengqin; Wan, Fanghao (Frontiers in Ecology and Evolution, 2023)
Alligator weed Alternanthera philoxeroides is a perennial, worldwide pernicious weed. It is an amphibious, trailing herb that is now widely distributed in tropical, subtropical and warm temperate countries and regions on six continents. The beetle Agasicles hygrophila is considered to be a classical biological agent used to control A. philoxeroides. As an oligophagous insect, its peripheral olfactory system contains odorant binding proteins (OBPs) and odorant receptors (ORs) that are extremely important for finding host plants and mates. In this study, we characterized the odorant receptor co-receptor of A. hygrophila (AhygOrco). Real-time quantitative PCR (qRT‒PCR) showed that AhygOrco was predominantly expressed in the antennae of both male and female adults, and the difference between male and female antennae was not significant. The RNA interference (RNAi) results showed that compared to the control, the injection of AhygOrco dsRNA strongly reduced the expression of AhygOrco by 90% in male beetles and 89% in female beetles. The mate-seeking and feeding behavior of AhygOrco-silenced beetles were significantly inhibited. Male adults were significantly less successful in finding a mate compared to the control group. Furthermore, host allocation abilities towards A. philoxeroides of both adults were significantly repressed. These results indicated that AhygOrco is associated with A. hygrophila feeding and mate-seeking and that inhibition of AhygOrco expression is one of the causes of reduced host and mate recognition in A. hygrophila . Meanwhile, the study provides support for exploring gene functions based on RNAi.